ANTILITHIATIC EFFECT OF CISSAMPELOS PAREIRA LEAVES IN AMMONIUM CHLORIDE AND ETHYLENE GLYCOL INDUCED UROLITHISIS IN RATS - Sayana, Suresh Babu; Chavan, Vasant R; Mudium, Raghunandan (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To study the antilithiatic activity of ethanolic extract of leaves of Cissampelos pareira (EELCP) in 2% ammonium chloride (AC) and 0.75% ethylene glycol (EG) induced urolithiasis in albino rats. Methods: Kidney stones were induced in rats by feeding drinking water mixed with 2% (AC) and 0.75% (EG) for 10 days. Stones were confirmed by the increased urinary levels of calcium, uric acid and decreased levels of magnesium and increased levels of serum creatinine and calcium. The rats were treated with 03 doses of EELCP i.e. 100 mg/kg, 200 mg/kg, 400 mg/kg respectively, orally in different groups of albino rats once daily for 10 days along with 2% (AC) and 0.75% (EG) containing drinking water. On 11th day, 3 rats from each group were kept in one metabolic cage and urine (pooled) collected for 24 hrs was subjected for assessment of various biochemical parameters. Blood was collected on the same day and analyzed for various parameters. Kidneys were observed for the histopathological changes. Results: Rats treated with 03 doses of EELCP significantly (p≤0.05) decreases the urinary calcium, uric acid and enhanced urinary magnesium levels, decreased serum calcium, creatinine and enhanced serum magnesium. Histopathology of kidneys in groups treated with EELCP at 200 mg/kg and 400 mg/kg doses revealed less tissue damage and the cytology of nephrotic tissue was almost similar to the control Group I rats. Conclusion: Results showed EELCP has shown significant antilithiatic effect against chemical induced urolithiasis in rats. Keywords: Cissampelos pareira, Leaf extract, Antilithiatic activity, Urolithiasis, Ethylene glycol.